Boiling of water droplet in glass–oil–water multiphase system. (October 2022) - He, Xiaotian; Cheng, Yiwei; Xu, Jinliang; Yu, Xiongjiang; Xie, Jian; Ma, Xiaojing; Ren, Yong
Highlights: Boiling of water droplet in glass-oil-water multiphase system was investigated. Two transition temperatures are determined experimentally and theoretically. Boiling bifurcation is found due to nucleation sites at solid-water or oil-water interface. The mode of boiling in oil and water is more violent than that for boiling in oil side only. Abstract: Boiling a volatile droplet in non-volatile liquid is complex because of various interface interactions in a solid–liquid–liquid system. Previous studies have reported explosive boiling and attributed this phenomenon to heterogeneous nucleation due to solid–liquid contact. In this study, we investigated the boiling of an approximately 2 mm-diameter water droplet in a silicon oil pool inside a glass container. Two transition temperatures were observed: 122.5 °C (for the transition from evaporation to boiling) and 160.0 °C (for the transition from the bubble growth on the oil side to that on both the oil and water sides). Moreover, four boiling modes were identified: evaporation (E), boiling in water (BIW: bubble nucleation at the glass–water interface and growth inside a drop), boiling in oil (BIO: bubble nucleation at the oil–water interface and growth in oil), and boiling in oil and water (BIOW: bubble nucleation at the oil–water interface and growth in oil and water). For the first time, boiling bifurcation was observed for drop boiling in a three-phase system. For the oil temperature ( T b ) in the range 122.5–160.0 °C, the boiling mode switches between BIW and BIO. In contrast, for T b exceeding 160.0 °C, either BIW or BIOW occurs. This bifurcation occurs because droplets prefer minimum activation energy between that for the bubble nucleation at the solid–water interface and that for the bubble nucleation at the oil–water interface. Interfacial instabilities were analyzed to explain why BIOW was more violent than BIW. This work presents a comprehensive understanding of droplet boiling in a three-phase system.